Pelatihan Penggunaan Media Pembelajaran Alat Ukur Sederhana : Penggaris, Jam Analog, dan Meteran Untuk Anak Usia Dini di PG & TK Terpadu Nurul Ma’arif (Penancangan Baru Serang) - Siti Hanan; Doto Doto; Lucky Setiawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Introduction to measuring tools is an important step in early childhood learning to help them understand basic measurement concepts such as length, weight and volume. Prescholl dan kindergarten at Nurul Ma'arif, this activity is designed with a creative and fun approach, so as to increase children's interest in learning. Through the use of simple measuring tools such as rulers, scales and measuring cups, children not only learn to recognize concrete sizes, but also develop cognitive, motor and logical skills. The implementation of this learning supports the achievement of holistic early childhood education goals, namely forming an intelligent, critical and innovative generation from an early age. The research used the classroom action research (PTK) method which consisted of two cycles, involving 5 children aged 4–5 years as subjects. Data was collected through observation, interviews and documentation, then analyzed descriptively qualitatively. The results of the research show that a play and experimental approach with simple measuring tools, such as rulers, stopwatches and weight scales, and clocks can increase children's understanding of the concept of measurement. Children become more active and enthusiastic in learning, with an increase in their ability to recognize length, determine body weight, recognize time and running speed. This research concludes that play and experimental approaches are effective for introducing measurement concepts to young children, as well as supporting the development of their fine motor and cognitive skills.